INSTABILITY OF ECONOMIC GROWTH IN THE COURSE OF TRANSITION - Natasha Trajkova (European Scientific Journal, ESJ, 2013)
In the conventional growth literature, long - run economic growth is usually described as a relatively steady pattern (single long –run trend) characterized by business cycles (short-run variations) around it. However, in this paper, we argue that this growth description that fits well developed countries’ growth paths does not accommodate well the economic growth paths observed in transition economies. Namely, the hypothesis tested in this paper is that the economic growth in the course of transition is characterized by breaks in the growth pattern. These breaks create a specific broken growth line instead of a single long-run growth trend.In order to test this assumption, the real data on GDP growth rates for 28 transition countries are observed. In addition, the univariate analysis for identifying structural breaks that is Perron’s version of the Augmented Dickey Fuller (ADF) test is applied in order to capture huge shifts in macroeconomic growth paths during transition, mainly related to the huge structural changes. Indeed, the empirical results confirm the suspicion of the broken GDP growth paths in the course of transition for most of the tested countries. This finding could alter the complete understanding of the growth process in the course of transition, not only when applying growth theory to, but also when undertaking growth empiric in the course of transition.